PREDICTIVE VALUE OF SERUM PROSTATE SPECIFIC ANTIGEN IN DETECTING BONE METASTASIS IN PROSTATE CANCER - Danarto, Raden; Astuti, Indwiani; Haryana, Sofia Mubarika (Indonesian Journal of Urology, 2021)
Objective: We determine the utility of Prostate Specific Antigen (PSA) for predicting the presence of skeletal metastasis on Bone Scan (BS) in prostate cancer patients. Material & Methods: Retrospective analysis of medical records of 70 consecutive prostate cancer patients subjected to bone scan during the last 2 years was done. 5 cases were excluded due to the following reasons: Serum PSA not available, hormonal or other therapy given prior to serum PSA measurement, and/or Bone Scan, and symptomatic for bone metastasis. In remaining 65 cases, PSA value and bone scan were evaluated. Results: BS was found to be positive in 20/65 (31%) and negative in 45(69%) patients. 24 (37%) had serum PSA > 100 ng/ml, 25 (38.5%) had PSA of 20‐100 ng/ml and only 16 (24.5%) had PSA < 20 ng/ml. Conclusion: Serum PSA < 20 ng/ml have high predictive value in ruling out skeletal metastasis. Our data are in corroboration with results from previous studies that BS should be performed only if PSA > 20 ng/ml. Using this cut‐off, unnecessary investigation can be avoided. Avoiding BS asymptomatic in this group of patients would translate into a significant cost‐saving and reduction in their psychological and physical burden.